2013
DOI: 10.1007/s00339-013-7668-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-temperature model for pulsed-laser-induced subsurface modifications in Si

Abstract: We investigated the laser-material interaction during the production of laser-induced subsurface modifications in silicon with a numerical model. Such modifications are of interest for subsurface wafer dicing. To predict the shape of these modifications, a two-temperature model and an optical model were combined. We compared the model results with experimental data obtained by focusing laser pulses in the bulk of silicon wafers using a microscope objective. This comparison revealed a good agreement between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…A comparison of the present results with those achieved by using an optical probe [11] underlines how the optical probe is sensitive to both carrier and lattice dynamics, even when the hydrodynamic expansion of the lattice becomes the dominant parameter to define the thermodynamic state of the system. Such sensitivity to both dynamical processes ineluctably complicates the data interpretation, in particular in cases similar to the present one, i.e., when the hydrodynamic expansion occurs on time scales similar to that typical of carrier dynamics [12,13,34]. However, since the EUV probing is more sensitive to the lattice dynamics, one can speculate on the possibility to perform a combined campaign of an optical/EUV transient reflectivity measurements, able to disentangle electron and lattice dynamics.…”
Section: Discussionmentioning
confidence: 71%
“…A comparison of the present results with those achieved by using an optical probe [11] underlines how the optical probe is sensitive to both carrier and lattice dynamics, even when the hydrodynamic expansion of the lattice becomes the dominant parameter to define the thermodynamic state of the system. Such sensitivity to both dynamical processes ineluctably complicates the data interpretation, in particular in cases similar to the present one, i.e., when the hydrodynamic expansion occurs on time scales similar to that typical of carrier dynamics [12,13,34]. However, since the EUV probing is more sensitive to the lattice dynamics, one can speculate on the possibility to perform a combined campaign of an optical/EUV transient reflectivity measurements, able to disentangle electron and lattice dynamics.…”
Section: Discussionmentioning
confidence: 71%
“…Requirement (2) is also unlikely to be violated. For a pulse energy of 90 µJ, no subsurface damage could be found [17], even though this energy value is two orders of magnitude beyond the required energy to form a subsurface modification [12,13,19].…”
Section: Laser Energy Absorption In Bulk Siliconmentioning
confidence: 93%
“…The volume that is heated by the laser may be larger than the focal volume, due to the diffusion of carriers, electronic heat conduction and lattice heat conduction. Since numerical simulations showed that diffusion effects have little effect during subsurface processing of silicon on a short nanosecond timescale [20], the extension of the laser-heated volume by diffusion has been neglected. A study of nanosecond surface heating of silicon also reported limited effects of carrier diffusion and electronic heat conduction [28].…”
Section: Laser Intensity Distribution and Modification Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations